Ethnobotany of Traditional Medicinal Plants by the Dayak Kanayatn Ahe Ethnic in Sumiak Hamlet, Landak Regency, West Kalimantan - Reni Patiola (Postgraduate, University of Mataram, 2023)
Indigenous people use wild plants in the forest to meet their daily needs, one of which is medicinal plants, but currently, the use of traditional medicines is decreasing due to the influence of the times. One of the communities that still uses plants as traditional medicine is the Dayak Kanayantn Ahe community. This tribe is one of the dominant tribes in the West Kalimantan region, but most of the medicinal plants used are not widely known, so it is necessary to carry out ethnobotanical research that focuses on studying the relationship between plants and human culture so that the plants used can be identified scientifically. This research approach is qualitative with descriptive methods. Data was obtained through observation, interviews, and documentation. The research results showed that there were 42 types of plants belonging to 31 families that could cure 46 types of diseases or symptoms. The types of herbaceous plants that are most widely used are found in the yard. The parts of the plant used as traditional medicine by the Dayak Kanayatn Ahe tribe are leaves, stems, roots, rhizomes, fruit, seeds, tubers, fruits, bark, and midribs. The decoction is one of the methods commonly used in processing medicinal plants.